#TITLE_ALTERNATIVE# - M. (NIM 10103016), EBENEZER
This final project discusses optimization in fishery. Fish population is assumed to grow according to logistic growth model. After the fishing starts, the population grows according to logistic model with harvesting. Its non trivial equilibrium solution is in fact a steady fish population for all of the future (this is sustainability). Continuity of solutions of the two models at t=s gives us the formula for s that indicates when the fishing starts. Next, we determine the number of fleet in order that maximizing the sustainable catch. The other two optimization problems use two different objective function, those are the total profit function and the profit per unit time. In each case the number of fleet can be determined in such a way that the corresponding objective function reaches a maximum.